Comparative study of the effects of bupropion and escitalopram on Internet gaming disorder. Issue 11 (27th October 2016) - Song, Jinuk; Park, Jeong Ha; Han, Doug Hyun; Roh, Sungwon; Son, Ji Hyun; Choi, Tae Young; Lee, Hyuk; Kim, Tae Ho; Lee, Young Sik
Abstract : Aim: We compared the efficacy of bupropion and escitalopram treatments in Internet gaming disorder (IGD) patients. Methods: We recruited 119 adolescents and adults with IGD. We treated these participants for 6 weeks in three groups as follows: 44 participants were treated with bupropion SR (bupropion group), 42 participants were treated with escitalopram (escitalopram group), and 33 patients without any medication were observed in the community (observation group). At baseline and at the 6‐week follow‐up visit, all subjects were evaluated using the Clinical Global Impression‐Severity Scale, the Young Internet Addiction Scale, the Beck Depression Inventory, the ADHD Rating Scale, and the Behavioral Inhibition and Activation Scales. Results: Both the escitalopram group and the bupropion group showed improvement on all clinical symptom scales after 6 weeks of treatment compared to the observation group. Additionally, the bupropion group showed greater improvement on scores for the Clinical Global Impression‐Severity Scale, the Young Internet Addiction Scale, the ADHD Rating Scale, and the Behavioral Inhibition Scale than the escitalopram group. Conclusion: Both bupropion and escitalopram were effective in treating and managing IGD symptoms. Moreover, bupropion appeared to be more effective than escitalopram in improving attention and impulsivity in IGD patients. In addition, attention and impulsivity seem to be important for the management of IGD.